Empowering women farmers in Uganda through ICTs - Okello, Dorothy (Technical Centre for Agricultural and Rural Cooperation, 2019)
Dorothy Okello, Coordinator of the Women of Uganda s Network (WOUGNET) walks us through the experience of the organisation, its evolution since its establishment in 2000, and how their long-term partnership with CTA has been crucial in helping women farmers access information.